2014
DOI: 10.1186/2193-1801-3-31
|View full text |Cite
|
Sign up to set email alerts
|

A study of Aspergillus niger- hydrolyzed cassava peel meal as a carbohydrate source on the histology of broiler chickens

Abstract: The purpose of this study is to investigate the effect of hydrolysed cassava peel inclusion as a replacement for maize in broiler chicken feedstuff on the histology of the internal organs of broiler chickens. Thirty six, two weeks old unsexed broiler chickens were used for the study in a feeding trial of forty two days. The chickens were randomly allocated to six dietary treatments A - F using a completely randomized design. Each treatment group contained two replicates of three broiler chickens. Group A chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
(13 reference statements)
2
9
1
2
Order By: Relevance
“…Penelitian tentang upaya penurunan serat kasar bahan baku pakan sudah banyak dilakukan antara lain melalui proses kimia (Abiola, Amalime, and Akadiri 2002;El Deek et al 2009;Sudiyani et al 2010) dan fermentasi menggunakan mikroba selulolitik (Song et al 2013;Adeyemo et al 2014;Sharawy, Goda, and Hassaan 2016). Proses kimia mempunyai kekurangan diantaranya biaya yang dikeluarkan cukup mahal dan tidak ramah lingkungan sedangkan fermentasi menggunakan mikroba menyebabkan banyak kehilangan bahan kering (biomass) dan munculnya efek samping yang ditimbulkan dari dinding sel mikroba itu sendiri yang tersusun atas polisakarida (peptidoglikan, glukan, dan/atau kitin).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Penelitian tentang upaya penurunan serat kasar bahan baku pakan sudah banyak dilakukan antara lain melalui proses kimia (Abiola, Amalime, and Akadiri 2002;El Deek et al 2009;Sudiyani et al 2010) dan fermentasi menggunakan mikroba selulolitik (Song et al 2013;Adeyemo et al 2014;Sharawy, Goda, and Hassaan 2016). Proses kimia mempunyai kekurangan diantaranya biaya yang dikeluarkan cukup mahal dan tidak ramah lingkungan sedangkan fermentasi menggunakan mikroba menyebabkan banyak kehilangan bahan kering (biomass) dan munculnya efek samping yang ditimbulkan dari dinding sel mikroba itu sendiri yang tersusun atas polisakarida (peptidoglikan, glukan, dan/atau kitin).…”
Section: Pendahuluanunclassified
“…Penelitian tentang pemanfaatan enzim selulase sudah mulai banyak dilaporkan (Stokes and Chen 1994;Beauchemin, Rode, and Sewaltl 1995;Cowan 1996;Hidayat et al 2005;Adeyemo et al 2014), tetapi masih sedikit informasi tentang pemanfaatan enzim selulase yang berasal dari B. subtilis untuk menurunkan serat kasar KUK. Hasil penelitian Melati et al (2014) (Miller, 1959), dan protein terlarut menggunakan metode UV-Vis (Stoscheck, 1990 Penambahan enzim selulase (25% dan 50%) memberikan pengaruh yang berbeda nyata terhadap penurunan kadar NDF dibandingkan kontrol (P<0,05), tetapi peningkatan dosis enzim selulase (dari 25% ke 50%) tidak memberikan pengaruh nyata terhadap penurunan kadar NDF (P>0,05).…”
Section: Pendahuluanunclassified
“…However, A. niger possesses the ability to produce fibredegrading enzymes (hemicellulases, hydrolases, pectinases), proteases, amylases, lipases and hydrolysed tannins as well as agents that can hydrolyse tannins [63]. A study was conducted Cassava 248 where A. niger was used to improve the nutritional quality of cassava peel meal in order to use it as a carbohydrate source for broiler chickens [64]. The findings showed that hydrolyzing cassava peal meal with A. niger reduced the influence of cyanide in the peel.…”
Section: Microbial Processing Of Cassava For Poultry Feedingmentioning
confidence: 99%
“…Adeyemo et al. () observed that hydrolyzed cassava peel meal and with soya bean oil addition could replace maize without adverse effects on broiler finisher. Feeding cassava peel meal at 150 g (Babatunde, ; Onyimonyi & Ugwu, ) and 225 g/kg diet (Tewe & Egbunike, ) had no adverse effect on broiler performance.…”
Section: Dietary Recommendations Of Peel Meals For Poultrymentioning
confidence: 99%
“…Cassava peel is high in fibre ranging from 140 to 340 g/kg (Adesehinwa et al, 2011;Aro et al, 2010;Kortei, Dzogbefia, & Obodai, 2014) with the fibre being mainly in the form of non-starch polysaccharides (NSP; Fakolade, 1997;Uthumporn, Nadiah, Izzuddin, Cheng, & Aida, 2017) which reduces its digestibility by poultry. Soluble sugar and crude fat contents of 680-700 g/kg and 3-20 g/kg, respectively, have been reported in cassava peel (Adeyemo, Sani, Aderibigbe, Abdurrasheed, & Agbolade, 2014;Kortei et al, 2014). The low-fat and high fibre contents contribute to the lower energy in cassava peel meal.…”
Section: Cassava Peelmentioning
confidence: 99%